2021
DOI: 10.3390/polym13040576
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Polyurethane Foams with Castor Oil Based Multifunctional Polyols for Improved Compressive Properties

Abstract: Currently, most commercial polyols used in the production of polyurethane (PU) foam are derived from petrochemicals. To address concerns relating to environmental pollution, a sustainable resource, namely, castor oil (CO), was used in this study. To improve the production efficiency, sustainability, and compressive strength of PU foam, which is widely used as an impact-absorbing material for protective equipment, PU foam was synthesized with CO-based multifunctional polyols. CO-based polyols with high function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…The structure and the properties of the rocket propellant composites are influenced by the composition and ratio of the blended polyols employed for the synthesis of the binder. Thus, it can be observed that the composite containing only SET, ECP_B5, displayed two glass transition temperatures, due to a stronger segregation [48] of the hard and the soft segments of the polyurethane employed in this type of composite. In this case, the polymeric chains of SET (castor-oil-based polyol), possessing considerably higher lengths, will generate larger zones where soft segments will merge.…”
Section: Resultsmentioning
confidence: 93%
“…The structure and the properties of the rocket propellant composites are influenced by the composition and ratio of the blended polyols employed for the synthesis of the binder. Thus, it can be observed that the composite containing only SET, ECP_B5, displayed two glass transition temperatures, due to a stronger segregation [48] of the hard and the soft segments of the polyurethane employed in this type of composite. In this case, the polymeric chains of SET (castor-oil-based polyol), possessing considerably higher lengths, will generate larger zones where soft segments will merge.…”
Section: Resultsmentioning
confidence: 93%
“…The density values of each type of foam went on increasing with the decrease in quantity of castor oil based PHU in the formulation. 74 The foams made from EDA and HMDA were flexible due to long chain aliphatic ethylene and hexamethylene structures. Perhaps their density values were in the range 155–215 kg m −3 .…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) General transesterification scheme of neem oil [ 14 ]. ( B ) Molecular weight distribution of neem oil and NOG.…”
Section: Figurementioning
confidence: 99%
“…89% directly as a polyol because of the intrinsic hydroxyl groups [ 11 , 12 , 13 ]. Moreover, castor oil-derived polyols with high functionalities can help to enhance the compressive strength of the PU foam [ 14 ]. The stable supply helps make castor oil a widely used raw material for industrial applications [ 15 ].…”
Section: Introductionmentioning
confidence: 99%